Reklama a čas - Srpová, Hana (Stylistyka, 2021)
The article compares old Czech printed advertisements (from the 30s of the 20,h centu- ry) with contemporary ones. Non-verbal means of expression were limited to black and white colours, various letter types and pictures (rather drawings than paintings and photo- graphs). Texts, written always in standard Czech, used mostly imperative, present tense, second person plural, third persons singular and plural, and various verbal and morpholo- gical means of intensification. Interested only in figures, the authors of old advertise- ments ignored tropes (frequent in contemporary ones), and they used rhyme rarely. Only several texts included slogan and company’s logo. The popular strategies were fear, experts’ recommendation, company tradition and export of the product.